Community Variations in Out-of-Hospital Cardiac Arrest Care and Outcomes in Texas. (4th March 2022) - Huebinger, Ryan; Jarvis, Jeff; Schulz, Kevin; Persse, David; Chan, Hei Kit; Miramontes, David; Vithalani, Veer; Troutman, Gerad; Greenberg, Robert; Al-Araji, Rabab; Villa, Normandy; Panczyk, Micah; et al.
Abstract: Background: Large and unacceptable variation exists in cardiac resuscitation care and outcomes across communities. Texas is the second most populous state in the US with wide variation in community and emergency response infrastructure. We utilized the Texas-CARES registry to perform the first Texas state analysis of out-of-hospital cardiac arrest (OHCA) in Texas, evaluating for variations in incidence, care, and outcomes. Methods: We analyzed the Texas-CARES registry, including all adult, non-traumatic OHCAs from 1/1/2014 through 12/31/2018. We analyzed the incidence and characteristics of OHCA care and outcome, overall and stratified by community. Utilizing mixed models accounting for clustering by community, we characterized variations in bystander CPR, bystander AED in public locations, and survival to hospital discharge across communities, adjusting for age, gender, race, location of arrest, and rate of witnessed arrest (bystander and 911 responder witnessed). Results: There were a total of 26, 847 (5, 369 per year) OHCAs from 13 communities; median 2, 762 per community (IQR 444-2, 767, min 136, max 9161). Texas care and outcome characteristics were: bystander CPR (43.3%), bystander AED use (9.1%), survival to discharge (9.1%), and survival with good neurological outcomes (4.0%). Bystander CPR rate ranged from 19.2% to 55.0%, and there were five communities above and five below the adjusted 95% confidence interval. Bystander AED use ranged from 0% to 19.5%, and there was one community below the adjusted 95% confidence interval. Survival to hospital discharge ranged from 6.7% to 14.0%, and there were three communities above and two below the adjusted 95% confidence interval. Conclusion: While overall OHCA care and outcomes were similar in Texas compared to national averages, bystander CPR, bystander AED use, and survival varied widely across communities in Texas. These variations signal opportunities to improve OHCA care and outcomes in Texas.